Theoretical and experimental evidence for a post-cotunnite phase transition in hafnia at high pressures - Al-Khatatbeh Yahya; Tarawneh Khaldoun; Al-Taani Hussein; Lee Kanani K.M. (Сверхтвердые материалы, 2018)
Using first-principles density-functional theory (DFT) computations, we have predicted a new post-cotunnite (OII) phase of hafnia (HfO₂) at high pressures. Our computations, using the generalized gradient approximation (GGA), predict a phase transition from OII to a Fe₂P-type structure at ~ 120 GPa (~ 140 GPa) with a slight volume collapse at the transition pressure of ~ 0.2 % (~ 0.1 %) between the two phases using the second- (third-) order Birch-Murnaghan equation of state, respectively. Використовуючи розрахунки з перших принципів теорії функціонала щільності, спрогнозовано отримання за високого тиску нової фази пост-хлориду свинцю (OII) – двоокису гафнію (HfO₂). Наші розрахунки, з використанням наближення узагальненого градієнта, передбачають фазовий перехід від OII до структури типу Fe₂P при ~ 120 ГПа (~ 140 ГПа) з невеликою зміною об’єму з перепадом тиску ~ 0,2 % (~ 0,1 %) між двома фазами з використанням другого (третього) порядку рівняння Birch-Murnaghan. Используя вычисления из первых принципов теории функционала плотности, предсказано получение при высоких давлениях новой фазы пост-хлорида свинца (OII) – двуокиси гафния (HfO₂). Наши расчеты, используя приближение обобщенного градиента, предсказывают фазовый переход от OII к структуре типа Fe₂P при ~ 120 ГПа (~ 140 ГПа) при небольшом изменении объема при давлении перехода ~ 0,2 % (~ 0,1 %) между двумя фазами с использованием уравнения состояния второго (третьего) порядка Birch-Murnaghan.